Evaluation of nurses' practices toward postoperative wound dressing in surgical wards - Atiyah, Hussein; Khudhur, Khalidah; hasan, Sadeq (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): The study aimed to assess the level of nursing performance and practices in terms of approaching ordistancing itself from the optimal performance criteria universally adopted within the variable dressing surgicalwounds of patients admitted to the surgical wards, and determine the relationship between the level of nurse'sperformance and socio-demographic characteristics of them in those wards.Methodology: A descriptive assessing design was adopted from November the 10th, 2010 until June the 1st, 2011 toassess the nursing care provided practices for the postoperative period within the variable dressing surgical wounds inthe complex of Medical City. Whereas the study was conducted in three hospitals; Baghdad Teaching Hospital, ALShahidGhazi Hariri for surgical specialties, and nursing home hospital. A Purposive "non- probability" sampleconsisting of (55) nurses from those who working in surgical wards at the time of data collection. The data werecollected after adapting AL-Ajloni questionnaire by the researchers that is dedicated to the purposes of the study andcomposed of two major parts; the first part includes the page of socio-demographic data which contains (6)paragraphs, and the second one includes the page of the major components of the study which contains (4) domainsin (39) sub-domain. The validity of the questionnaire was determined by (7) experts in the specialty field. While, thereliability of the questionnaire was determined by calculating the correlation coefficient (Pearson), which wasstatistically acceptable value (r = 0.86). Data were collected through direct observant approach by the mean of thedesigned practice checklist. Thereafter, the data were analyzed through the application of descriptive analysismeasures (frequencies and percentages), as well as weighted arithmetic mean and Pearson correlation coefficient byusing (SPSS) Version 16.Results: The findings of the study indicated that academic nurses had performed adequate practices relative topostoperative wound dressing than practical ones. All nurses regardless of their gender had performed almost at thesame level of practices relative to postoperative wound dressing. Older nurses demonstrated inadequate practicesconcerning postoperative wound infection precautions. The quality of nurse's performance regarding postoperativedressing procedure was strong positive relationship with level of education. Nurses who had participated in trainingsessions performed the same practices of others without it.29Nurses' practices and postoperative wound dressingRecommendations: standards practice guide lines should be available for every nurse in hospital; furthermore strictnosocomial infection control precaution should be followed by health care providers. In addition thorough advancedtraining courses should be available for nurses dedicated in its nature toward standards ideal safe practice